(untitled) (Canadian Medical Education Journal, 2016)
The increasing globalization of the medical profession has influenced health policy, health human resource planning, and medical regulation in Canada. Since the early 2000s, numerous policy initiatives have been created to facilitate the entry of international medical graduates (IMGs) into the Canadian workforce. In Ontario, the College of Physicians and Surgeons of Ontario (CPSO) developed alternative licensure routes to increase the ability of qualified IMGs to obtain licenses to practice. The current study provides demographic and descriptive information about the IMGs registered through the CPSO’s alternative licensure routes between 2000 and 2012. An analysis of the characteristics and career trajectories of all IMGs practicing in the province sheds light on broader globalization trends and raises questions about the future of health human resource planning in Canada. As the medical profession becomes increasingly globalized, health policy and regulation will continue to be influenced by trends in international migration, concerns about global health equity, and the shifting demographics of the Canadian physician workforce. Implications for future policy development in the complex landscape of medical education and practice are discussed.